2017
DOI: 10.1186/s12894-017-0211-9
|View full text |Cite
|
Sign up to set email alerts
|

Benign prostatic enlargement can be influenced by metabolic profile: results of a multicenter prospective study

Abstract: BackgroundIn last years Metabolic Syndrome (MetS) has been closely associated to Benign Prostatic Enlargement (BPE) Aim of our study is to evaluate the effect of MetS and each single MetS parameter on prostate growth in men surgically treated for BPE.MethodsOverall, 379 men were prospectively enrolled in two tertiary referral centers. Calculated prostate volume (PV) was measured with transrectal US defining the antero-posterior (AP), the cranio-caudal (CC) and the latero-lateral (LL) diameters through the elli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…As previously reported, we observed an association between MetS and/or most of its individual criterion with lower circulating levels of testosterone and higher circulating levels of CRP. Furthermore, the analysis of the different clinical characteristics comparing patients with and without MetS revealed that patients with MetS had slightly higher prostate volume compared with patients without MetS, which is consistent with a recent report indicating an association of MetS parameters with benign prostatic enlargement in men surgically treated for this pathology . These data might suggest that some component of the MetS could be connected with the prostatic growth and, therefore, given that the prevalence of MetS is increasing worldwide, the clinical control of MetS should be considered in patients at risk of PCa.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As previously reported, we observed an association between MetS and/or most of its individual criterion with lower circulating levels of testosterone and higher circulating levels of CRP. Furthermore, the analysis of the different clinical characteristics comparing patients with and without MetS revealed that patients with MetS had slightly higher prostate volume compared with patients without MetS, which is consistent with a recent report indicating an association of MetS parameters with benign prostatic enlargement in men surgically treated for this pathology . These data might suggest that some component of the MetS could be connected with the prostatic growth and, therefore, given that the prevalence of MetS is increasing worldwide, the clinical control of MetS should be considered in patients at risk of PCa.…”
Section: Discussionsupporting
confidence: 88%
“…enlargement in men surgically treated for this pathology. 25 These data might suggest that some component of the MetS could be connected with the prostatic growth and, therefore, given that the prevalence of MetS is increasing worldwide, the clinical control of MetS should be considered in patients at risk of PCa.…”
Section: Mets Crp and Testosterone Levels As Predictive Factors Ofmentioning
confidence: 99%
“…21 Similarly, in the meta-analysis study of Zou et al 4 that identified that the presence of MetS increased PV, the author posited that hyperinsulinemia, proinflammatory cytokines, and androgens may be linked with MetS and increased PV. A study also found that the number of MetS components (0 to 5) and the presence of MetS were significantly associated with PV levels 22 ; moreover, we also found that as the number of abnormal MetS components increases, the PV presents a trend of progressive increase (shown in Supporting Information Materials, n = 506). Zhang et al 23 reported that patients with MetS showed a significantly larger PV than non-MetS individuals and considered that insulin and insulin resistance were significant risk factors for prostate enlargement.…”
Section: Furthermore As Shown Insupporting
confidence: 77%
“…MetS is a complex disorder and worldwide epidemic, which describes the combination or clustering of several metabolic abnormalities, including central obesity, dyslipidemia, hypertension, insulin resistance with compensatory hyperinsulinemia, and glucose intolerance. Although the exact nature of the association between MetS and LUTS is still not completely understood, MetS has been associated with an increased risk of LUTS and particularly of storage LUTS (multivariate odds ratio [OR]: 1.782; 95% confidence interval [CI]: 1.045‐3.042; P = .030) …”
Section: Introductionmentioning
confidence: 99%
“…Although the exact nature of the association between MetS and LUTS is still not completely understood, MetS has been associated with an increased risk of LUTS and particularly of storage LUTS (multivariate odds ratio [OR]: 1.782; 95% confidence interval [CI]: 1.045-3.042; P = .030). [9][10][11] Smoking through different biological mechanisms including autonomic nervous system activity has been involved in LUTS pathogenesis. 12 Indeed, heavy smoking (defined as >50 pack-years) was found to increase the risk of LUTS exacerbation and can affect storage and voiding symptoms.…”
Section: Introductionmentioning
confidence: 99%